Contribution to the syntaxonomy of plant communities with insular endemic species of genus Brassica (southern Croatia) - Jasprica, Nenad; Stamenković, Vanja (Hacquetia, 2023)
Communities with constant presence of two insular endemic species of genus Brassica (B. cazzae Ginzb. et Teyber, B. mollis Vis.) were studied on the small south-eastern Adriatic islands and islets (South Croatia), following the Braun-Blanquet approach. From a total of 51 phytosociological relevés, mostly collected in the period from 2020 and 2022, eight associations and three subassociations belonging to seven alliances and six classes were identified. Brassica cazzae and B. mollis occur in a variety of habitat types (i) in bare or very shallow soils on which halophilous and halotolerant communities of the Limonion anfracti-cancellati and Anthyllidion barbae-jovis mostly thrive, (ii) on rocky crevices and cliffs with rupicolous chasmophytic vegetation of the Centaureo cuspidatae-Portenschlagiellion ramosissimae, (iii) within woody vegetation of the Pistacio lentisci-Pinion halepensis, maquis of the Oleo-Ceratonion siliquae and garrigues of the Cisto cretici-Ericion manipuliflorae, and (iv) grasslands of the Chrysopogono grylli-Koelerion splendentis. Two associations (Plantagino holostei-Limonietum cazzae, Brassico mollis-Anthyllidetum barbae-jovis) and one subassociation (Centaureetum ragusinae limonietosum cazzae) are described for the first time.